A Umbanda é para todos, mas nem todos são para a Umbanda : multiplicidade, pluralismo religioso e gênero em um terreiro de Umbanda Esotérica - Bianca Zacarias França (2021)
This dissertation, organized in three chapters, is the result of an ethnographic work in an Umbanda Esoterica’s terreiro in the city of Belo Horizonte, Minas Gerais. The objective is to understand how such a multiple cosmology, defined by Umbandists as afro-universalist, crosses the composition and topology of territorial forces, such as the terreiro and the body, which are polarized by gender, as a ritual organizer, and populated by other beings. Exu and time appear as great promoters of encounters that cross paths - lines of biographical strength - of the mediums with the terreiro and their guides. Showing us that not everything that comes together is mixed, the pluralist or polytheistic style seems to set the tone of the art of uniting difference without ending heterogeneity or losing its Umbanda belonging.